A RETROSPECTIVE STUDY ON PREVALENCE OF MISSING MAXILLARY ANTERIORS AMONG YOUNG ADULT (Journal of Pharmaceutical Negative Results, 2022)
Importance of tooth loss, still ranked among the hundred health conditions. The anterior teeth play an important role in the functions of lip support, esthetics and phonetics. Loss of anterior teeth has major detrimental social implications for the sufferer and significantly affects the normal social integration. To evaluate the prevalence of maxillary anterior missing teeth in young adults (18-35 years old). A total of 1312 patients of 18-35 years old with maxillary missing anterior teeth who visited Private Dental Hospital. Data collected and tabulated in excel. Data analyzed done usingSPSS Software. The overall prevalence of the anterior missing tooth is 46.7%. The common frequency of age with missing anterior is between 25-30 years old patients. The prevalence of gender with missing anterior tooth is male of 68.5%. The most common prosthesis treatment found to be FPD (46.9%) and least common prosthesis treatment is implant supported FPD (1.5%).The most common missing tooth is Maxillary Right Central Incisor (30.6%) and the least common is Maxillary Left Canine (5.7%). There is no significant association between prosthesis treatment and age, gender and missing teeth. There is a higher prevalence of tooth loss in maxillary anteriors among young adults.